Numerical calculation of bridge seismic response considering beam-block collision effect - Shuijiang, Wang (Revista de la Construcción. Journal of Construction, 2019)
During earthquake, collision between the beam and the block is the direct factor causing damage to the block. To better study the problem and the variation of seismic response in transverse direction of bridge arising from collision, it is necessary to perform quantitative analysis. The Kelvin contact unit model and the single-step Houbolt (SSH) numerical calculation method are adopted for the problem in order to deduce the numerical calculation method and procedures of the bridge seismic response considering beam-block collision effect. MATLAB is used to prepare corresponding program. Through comparison of the calculation result with the test data in related references, it is seen that the calculation method put forward in the paper is of high calculation efficiency and accurate result. In addition, a specific example is made to validate the practicability of this method.